Intercultural management in practice : learning to lead diverse global organizations - Chavan, Meena; Taksa, Lucy (Emerald Publishing Limited, 2021)
Modern-day business leaders need to manage diverse global organisations and teams that work in international contexts. Intercultural Management in Practice will assist organisations of all types to manage diversity and promote inclusion in their national and international operations and markets. The themes explored encompass cross-cultural interaction among expatriates, global mindset for negotiators, decision makers and teams that work in international contexts. This book will enhance understanding of how cultural brokering is enacted as part of the labour market integration for refugees and the cultural context of learning styles both of which contribute to the design of culturally-appropriate training and development strategies and enhance the performance of employees and organizations. In these ways this engaging and informative text provides insights that enable effective responses to existing and new challenges. This book educates and informs students and professionals on Intercultural Management in the business world by providing a foundation for the building of intercultural competence and learning how to manage cultural diversity and intercultural relations and interactions.